Intentional sustainable communities and sustainable development goals: from micro-scale implementation to scalability of innovative practices - Nogueira, Carla; Marques, João Filipe; Pinto, Hugo (Journal of environmental planning and management, 2024)
Intentional sustainable communities (ISCs) are commonly described as micro-based community initiatives that seek to develop sustainable lifestyles with low environmental impact. More recently, they have been analyzed as laboratories for the emergence of innovation, namely social innovation, and as actors that can contribute to sustainable transitions. This reinforces their role as pressure agents and as microscale communities of practice. Theoretically, it is argued that this scalability of innovation dynamics requires a multi-level and multi-actor perspective, mechanisms of reciprocity and that actors are not isolated and atomized. These mechanisms, such as networks, are crucial for the dissemination of sustainability practices and for increasing their potential impact. This article argues that these communities can also be important micro agents in achieving Sustainable Development Goals (SDGs) and to mainstream the importance of scaling their innovation practices. To this end, the study uses quantitative data from a survey applied to the ISCs in Europe. The data corroborates the communities' contribution to the SDGs, namely to SDG12, SDG13 and SDG16 and presents the collaboration network structure established within these communities.